STRATEGI PENDAMPINGAN KEGIATAN KOMUNITAS BELAJAR BERBASIS PROGRAM SEKOLAH PENGGERAK DI KABUPATEN SUMEDANG - Asep Wawan Jatnika; Rokayah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research entitled Mentoring Strategy for Learning Community Activities Based on the Sekolah Penggerak Program in Sumedang Regency is motivated by the results of the Learning Community Mentoring workshop at the sekolah penggerak which aims to describe the implementation and profile of the effectiveness of mentoring activities for teachers and school heads in the Sekolah Penggerak Program in Sumedang Regency. The method used is descriptive analytical and evaluative of mentoring activities for learning community activities at school. Based on the research results, it can be concluded that mentoring for learning community activities at school based on the Sekolah Penggerak Program can be implemented well with a maximum level of success. This can be seen from (1) the establishment of a learning community, (2) increased activity in building a learning community, (3) maximum success in building a learning community, (4) the resolution of challenges and obstacles in building a learning community. (5) identification of ways to overcome challenges and obstacles in building a learning community, and (6) Teachers and principals have played an active role in building the quality of the learning community at school.